Carbon Footprint Assessment Model for Chinese Dairy Sector - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The software was developed and tested using data collected from 6 regions (North, Northeast, East, Central and southern, Northwest and Southwest of China) including 16 provinces/cities and ready to use for emission estimation in the Chinese dairy sector